2021
DOI: 10.3390/ijgi10080493
|View full text |Cite
|
Sign up to set email alerts
|

Subjectively Measured Streetscape Perceptions to Inform Urban Design Strategies for Shanghai

Abstract: Recently, many new studies applying computer vision (CV) to street view imagery (SVI) datasets to objectively extract the view indices of various streetscape features such as trees to proxy urban scene qualities have emerged. However, human perception (e.g., imageability) have a subtle relationship to visual elements that cannot be fully captured using view indices. Conversely, subjective measures using survey and interview data explain human behaviors more. However, the effectiveness of integrating subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…A number of recent studies have demonstrated how the use of computer vision and machine learning (ML) in quantifying social science fundamentals can effectively predict, undertake and illustrate micro-urban analysis of environments at a macro scale (Naik et al 2014, Qiu et al 2021, Yin and Wang, 2016. Naik et al (2014), for example, successfully measured perceived safety, utilising and converting survey data on urban perceptions to predict the perceived safety scores of streets across 21 cities worldwide (Qiu et al 2021). Qiu et al (2021) et al, 2012).…”
Section: Computer Vision and Machine Learning In Street Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of recent studies have demonstrated how the use of computer vision and machine learning (ML) in quantifying social science fundamentals can effectively predict, undertake and illustrate micro-urban analysis of environments at a macro scale (Naik et al 2014, Qiu et al 2021, Yin and Wang, 2016. Naik et al (2014), for example, successfully measured perceived safety, utilising and converting survey data on urban perceptions to predict the perceived safety scores of streets across 21 cities worldwide (Qiu et al 2021). Qiu et al (2021) et al, 2012).…”
Section: Computer Vision and Machine Learning In Street Measuresmentioning
confidence: 99%
“…Naik et al (2014), for example, successfully measured perceived safety, utilising and converting survey data on urban perceptions to predict the perceived safety scores of streets across 21 cities worldwide (Qiu et al 2021). Qiu et al (2021) et al, 2012). Despite current data and research highlighting the common factors that encourage or deter cycling activity, further analysis is required to understand their correlations and affect in determining the bicycle-friendliness of an environment.…”
Section: Computer Vision and Machine Learning In Street Measuresmentioning
confidence: 99%
See 3 more Smart Citations